Novel Therapies for Alport Syndrome - Chavez, Efren; Rodriguez, Juanly; Drexler, Yelena; Fornoni, Alessia (Frontiers in Medicine, 2022)
Alport syndrome (AS) is a hereditary kidney disease associated with proteinuria, hematuria and progressive kidney failure. It is characterized by a defective glomerular basement membrane caused by mutations in type IV collagen genes COL4A3/A4/A5 which result in defective type IV collagen α3, α4, or α5 chains, respectively. AS has three different patterns of inheritance: X-linked, autosomal and digenic. In a study of CKD of unknown etiology type IV collagen gene mutations accounted for most cases of hereditary glomerulopathies which suggests that AS is often underrecognized. The natural history and prognosis in patients with AS is variable and is determined by genetics and environmental factors. At present, no preventive or curative therapies exist for AS. Current treatment includes the use of renin-angiotensin-aldosterone system (RAAS) inhibitors which have been associated with a slower CKD progression and longer life expectancy. Ramipril use was associated with later onset of ESKD and was recently demonstrated to be safe and effective in children and adolescents, supporting that early initiation of RAAS blockade is very important. Mineralocorticoid receptor blockers might be favorable for patients who develop “aldosterone breakthrough”. While the DAPA-CKD trial suggests a beneficial effect of SGLT2 inhibitors in CKD of non-metabolic origin, only a handful of patients had Alport in this cohort, and therefore conclusions can’t be extrapolated for the treatment of AS with SGLT2 inhibitors. Advances in our understanding on the pathogenesis of Alport syndrome has culminated in the development of innovative therapeutic approaches that are currently under investigation. We will provide a brief overview of novel therapeutic targets to prevent progression of kidney disease in AS. Our review will include bardoxolone methyl, an oral NRf2 activator; lademirsen, an anti-miRNA-21 molecule; sparsentan, dual endothelin type A receptor (ETAR) and angiotensin 1 receptor inhibitor; atrasentan, oral selective ETAR inhibitor; lipid-modifying agents, including inducers of cholesterol efflux transporter ATP-binding cassette A1, discoidin domain receptor 1 inhibitors and osteopontin blocking agents; the antimalarial drug hydroxychloroquine; the antiglycemic drug metformin and the active vitamin D analogue paricalcitol. Future genomic therapeutic strategies such as chaperone therapy, genome editing and stem cell therapy will also be discussed.